Sex, crime and entertainment: Images of LGBT in the Indonesian news media. Issue 146 (2nd January 2022) - Hegarty, Benjamin
ABSTRACT: Images linking 'LGBT' to sexually motivated crime are a common feature of reporting in the Indonesian online news media. In particular, 'gay sex parties' are a spectacle shaped by the images produced by journalists in collaboration with the police. This combination of crime and entertainment plays a crucial role in managing both in what ways LGBT is seen and by extension what is defined as belonging to the public sphere. Media images of raids take the form of videos and photographs, press conferences and reconstructions filmed at the crime scene. Although same-sex sexual acts between consenting adults are not a crime in Indonesia, the 2008 Pornography Law and various regional regulations do provide scope for detaining people on public decency grounds. However, the connection between sex and crime as a form of entertainment in which the police are central protagonists is shaped by histories of visual power that can be traced to the authoritarian New Order. By contextualising and interpreting media images of a police raid on a 'gay sex party' in September 2020, I describe how the genre conventions and affective force of images of LGBT are central to the state's governance of the public sphere. Considering the relationship between sex, crime and entertainment helps to address the central role played by both unruly images and media power in regulating the boundaries of political participation and claims for justice.